Knowledge about informed consent among doctors in postgraduate courses in Bangladesh - Mamun, Kazi Taib; Mahboob, Nabeela; Mahmud, Mohammad Abdullah Al; Zaman, K (IMC Journal of Medical Science, 2020)
Background and objectives: Informed consent is now accepted as the cornerstone of medical practice and research. Concept of consent is an endeavor by which the patient can take part in clinical judgment concerning their treatment and protects patient and doctors against any litigation. However, in research informed consent is not merely a form that is signed, but is a process in which the participant has an understanding of the research and its risks. In view of this, the objective of the study was to assess the knowledge regarding informed consent among the doctors pursuing postgraduate courses in a medical institute in Bangladesh. Methodology: A descriptive cross sectional study was carried out among 160 postgraduate medical students in Dhaka city. A self-administered structured questionnaire consisting of 36 questions was used to assess their knowledge regarding informed consent. The response format was based on a 3-point Likert scale. Frequency distribution was used for statistical analysis. Results: The age range of the participants was from 25-40 years. Of the total participants, 48% were males and 42% were females. Majority of the respondents acknowledged the importance of an informed consent and 86.3% of the doctors agreed that only verbal consent was not adequate. Only 66.2% agreed that consent for participation in research should always be voluntary and informed. Majority (76.9%) agreed not to recruit individuals with mental or behavioral disorders not capable of giving adequately informed consent. Only 27.5% were aware that assent should be taken from children participating in a research. Out of total participants, 71.2% and 81.2% agreed that the participants should be informed about the laboratory test results. Management/referral must be ensured in case of abnormal test results respectively. For genetic research, 88.1% and 81.3% agreed for pre- and post-counseling respectively. Conclusion: There is need to initiate further educational programs to aware the doctors of the importance of informed consent in research, clinical practice and patient care. Ibrahim Med. Coll. J. 2020; 14(1): 26-35